ANALYSIS OF FACTORS AFFECTING THE INCREASE OF CUSTOMER LOYALTY IN BATIK BOGOR Tradisiku - Annuridya Rosyidta Pratiwi Octasylva (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2021)
In Bogor city, there have been many permits that offer typical batik batik of Bogor. one of them isBogor batik Tradisiku, Tradisiku Bogor batik is a pioneer of typical batik Bogor. But now there are more and more competitors for Bogor Batik Tradisiku, that impact to the decline in sales ofBogor batik Tradisiku, Thus Spake demanding Bogor batik Tradisikuto continue fighting in intense competition. Therefore, the purpose of this study is to analyze factors that Affect customer satisfaction and relationship quality (customer trust and customer commitment) ofBogor batik Tradisiku, Based on the results of the study, using Partial Least Square (PLS), it is known that Satisfaction with customer commitment is not significant. This is Because The value of P values has exceeded 0:05 or 5 percent. Customer trust relationships with loyalty are significant. This is due to the value of P values below 0:05 or 5 percent.